Keberagaman Gender dan Pengaruhnya Terhadap Kinerja Keuangan Perusahaan Perbankan Konvensional Indonesia - Heavenly, Felicia Tyrenz; Susanto, Liana (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
This study was conducted with the aim of obtaining empirical evidence on the effect of gender diversity which is represented through woman’s leadership and proportion on board of directors, commissioners, and audit committee on the financial performance of conventional Indonesian banking companies listed on the Indonesia Stock Exchange during the period of 2020 to 2023. In this study, 40 companies and 133 samples was chosen by using the purposive sampling method with specific criterias. Secondary data in this research was obtained through firm’s financial statement that are published on the IDX website. Data analysis for this study was carried through Multiple linear regressions with the help of SPSS 27.0. It is founded that simultaneously, all three independent variables managed to influence a company’s financial performance. Partially, the proportion of women of women on the board of directors has no effect on the company’s financial statement, white the proportion of women on the board of commissioners has a significant negative effect towards company’s financial performance. Furthermore, the proportion of women on the audit committee has a significant positive effect on the company’s financial performance. This findings suggest that leadership and the proportion of women in a company is a factor that needed to be considered because of their ability in influencing company’s financial performance that leads to the stability and profitability of the company itself.